PENGARUH INFLASI REGIONAL TERHADAP NILAI TUKAR PETANI (NTP) DI PROVINSI SUMATERA BARAT - Fitri Rahmawati; Fandy Triawan (Media Riset Ekonomi Pembangunan (MedREP), 2026)
This study analyzes the effect of regional inflation on the Farmers Terms of Trade (FTT) in West Sumatra Province for the period 2010:Q1–2024:Q4. Using the Autoregressive Distributed Lag (ARDL) method with quarterly data, this study aims to examine both short-run and long-run dynamics of the relationship between regional inflation and farmers' welfare as measured by FTT. The results of the F-Bounds Test confirm the existence of a long-run cointegration relationship. In the long run, regional inflation has a significant negative effect on FTT, with a coefficient of −222.32, indicating that a 1 percent increase in regional inflation decreases FTT by 222.32 index points. In the short run, regional inflation also has a significant negative effect at the current period, while lagged responses show a complex oscillation pattern reflecting delayed price pass-through effects. The Error Correction Term coefficient of −1.0079 confirms that the system adjusts toward long-run equilibrium at approximately 100.79 percent per quarter. These findings confirm that persistent inflationary pressure consistently erodes farmers' purchasing power through rising household consumption costs and agricultural input costs. Policy recommendations include strengthening regional price stabilization through the Regional Inflation Control Team (TPID), improving agricultural input subsidies, and enhancing market information systems. Keywords: Regional Inflation, Farmers' Terms of Trade, ARDL, West Sumatra, Agricultural Welfare.